Increasing LFA-1 Expression Enhances Immune Synapse Architecture and T Cell Receptor Signaling in Jurkat E6.1 Cells - Cassioli, Chiara; Balint, Stefan; Compeer, Ewoud B.; Felce, James H.; Gamberucci, Alessandra; Della Bella, Chiara; Felce, Suet Ling; Brunetti, Jlenia; Valvo, Salvatore; Pende, Daniela; D’Elios, Mario M.; Moretta, Lorenzo; et al. (Frontiers in Cell and Developmental Biology, 2021)
The Jurkat E6.1 clone has been extensively used as a powerful tool for the genetic and biochemical dissection of the TCR signaling pathway. More recently, these cells have been exploited in imaging studies to identify key players in immunological synapse (IS) assembly in superantigen-specific conjugates and to track the dynamics of signaling molecules on glass surfaces coated with activating anti-CD3 antibodies. By comparison, Jurkat cells have been used only scantily for imaging on supported lipid bilayers (SLBs) incorporating laterally mobile TCR and integrin ligands, which allow to study synaptic rearrangements of surface molecules and the fine architecture of the mature IS, likely due to limitations in the assembly of immune synapses with well-defined architecture. Here we have explored whether upregulating the low levels of endogenous LFA-1 expression on Jurkat E6.1 cells through transduction with CD11a-and CD18-encoding lentiviruses can improve IS architecture. We show that, while forced LFA-1 expression did not affect TCR recruitment to the IS, E6.1 LFA-1high cells assembled better structured synapses, with a tighter distribution of signaling-competent TCRs at the center of the IS. LFA-1 upregulation enhanced protein phosphotyrosine signaling on SLBs but not at the IS formed in conjugates with SEE-pulsed APCs, and led to the constitutive formation of an intracellular phosphotyrosine pool co-localising with endosomal CD3. This was paralleled by an increase in the levels of pZAP-70 and pErk both under basal conditions and following activation, and in enhanced Ca2+ mobilization from intracellular stores. The enhancement in early signaling E6.1 LFA-1high cells did not affect expression of the early activation marker CD69 but led to an increase in IL-2 expression. Our results highlight a new role for LFA-1 in the core architecture of the IS that can be exploited to study the spatiotemporal redistribution of surface receptors on SLBs, thereby extending the potential of E6.1 cells and their derivatives for fine-scale imaging studies.